Big bester production probability study - Baradaran Noveiri, Shahrouz; Pourkazemi, M.; Hassanzade Saber, M.; Yazdani Sadati, M.A.; Kazemi, R.; Mohammadi Parashkuh, H.; Nowrouz Fashkhami, M.R.; Alipor, A.R.; Hallajiyan, A. (Iranian Fisheries Science Research Institute, 2017)
Aquaculture of sturgeon species and their hybrids is being considered as an important substitution for sturgeon catch due to highly decrease of natural populations, artificial propagation and fingerling release in the sea. In this study, big bester, a new hybrid sturgeon (female beluga × male bester) was produced for the first time in IRAN. Sperm of 7350 ± 1682 kg male bester was used to fertilize the eggs of one 54 kg female Huso huso. The fries of big bester and control treatment of beluga were fed by artificial concentrated food (48-50% protein and 15-17% fat) after egg yolk absorbance, a period of feeding on Artemia and Daphnia. Results showed that rearing and feeding of bester broods was efficient to reach the fish to maturation stage and there is an opportunity to collect qualified ova and sperm from F1 generation. Meanwhile sex determination and maturity assessment of gonads were successfully done via laparoscopy method. The comparison of produced big bester fingerlings with control beluga fingerling showed that the weight of big bester fingerlings has not significant difference with beluga's (p< 0.05) at the age up to 2 months. At 3 months of age, beluga fingerlings showed higher weight (p>0.05), but there are faster growth rate in big bester fingerlings from 3 months of age up to 5 months (p>0.05) in comparison with belugas fingerlings. Meanwhile no statistically significant difference was found between length of big bester and beluga fingerlings among any age. The results of current study showed the potential of rearing male bester to produce matured broods and collection of their sperm for big bester production.